Neurological soft signs in the clinical course of schizophrenia: results of a meta-analysis - Bachmann, Silke; Degen, Christina; Geider, Franz Josef; Schröder, Johannes (Frontiers in psychiatry, 2014)
Neurological soft signs (NSS) comprise subtle deficits in sensory integration, motor coordination, and sequencing of complex motor acts, which are typically observed in the majority of schizophrenia patients, including chronic cases and neuroleptic-naïve first-episode patients. However, recent studies clearly demonstrate that NSS are not a static feature of schizophrenia but vary in the clinical course of the disorder. This effect was investigated in a meta-analysis based on 17 longitudinal studies published between 1992 and 2012.
Gesehen am 14.10.2020